(untitled) (Academia Journal of Medicine, 2018)
Background: The most significant and common cause of anemia is iron deficiency. Hence, we planned the present study to assess the prevalence of iron deficiency anemia among known population. Subjects and Methods: A total of 350 subjects who reported to the department of internal medicine for routine checkup were included in the present study.Blood samples were obtained from all the subjects and were sent to central laboratory for the assessment of blood hemoglobin levels. Criteria described in the past literature were used for categorizing patients with iron deficiency anemia. Females with mean hemoglobin concentration less than 11.5 g/dL, and males with mean hemoglobin concentrations less than14 g/dL were categorized as anemic.6 All the results were analyzed by SPSS software. Results: Overall prevalence of iron deficiency anemia in the present study was 15.28 percent. The overall prevalence of iron deficiency anemia was found to be higher among subjects with more than 60 years of age. Also, significantly higher prevalence of iron deficiency anemia was found among females. Conclusion: Prevalence of iron deficiency anemia was found to be higher among females and illiterates. Therefore health education programs are recommended in future for increasing the awareness of adverse events associated with iron deficiency anemia among general population.